MAKE OR BUY? STRATEGI OUTSOURCING UNTUK MENCIPTAKAN COMPETITIVE ADVANTAGE - Zaroni . (Center for Economic Studies Universitas Katolik Parahyangan, 2005)
Most companies can substantially leverage their resources through strategic outsourcing by: (1) developing a few well-selected core competencies of significance to customers and in which the company can be best-in-world; (2) focusing investment and management attention on them; and (3) ,strategically outsourcing many other activities where it cannot or need not be best. There are always some inherent risks in outsourcing, but there are also risks and costs associated with insourcing. When approached within a genuinely strategic framework, using the variety of outsourcing options available, and analyzing the strategic issues developed here, companies can overcome many of the costs and risks. When intelligently combined, core competency and extensive outsourcing strategies provide improved returns on capital, lowered risk, greater flexibility, and better responsiveness to customer needs at lower cost.